2010
DOI: 10.3109/01421590903434169
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing social responsibility through community service-learning: Lessons learned from a pilot project

Abstract: CSL can play an important role in nurturing a purposeful sense of social responsibility among future practitioners. Our study enabled the implementation of an innovative longitudinal course (professionalism and community service) in all 4 years of the dental curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 25 publications
4
84
0
3
Order By: Relevance
“…This confirms the importance of 'witnessing' the social determinants that affect peoples' lives "by observing and acquiring firsthand knowledge" (Dharamsi et al, 2010).…”
Section: [Here] You Just Get To See a Lot More Of What Goes On In supporting
confidence: 50%
“…This confirms the importance of 'witnessing' the social determinants that affect peoples' lives "by observing and acquiring firsthand knowledge" (Dharamsi et al, 2010).…”
Section: [Here] You Just Get To See a Lot More Of What Goes On In supporting
confidence: 50%
“…For example, one study, which determined an increased likelihood of medical students becoming physicians for underserviced areas, integrated a longitudinal curriculum involving all four year of medical school [13]. Nevertheless, research has shown a benefit from the DPAS course, and we feel that the DPAS course, despite lasting only one year, has positively impacted our experience [8,9]. Furthermore, our group continues to be informally involved with the VSSL and attends monthly games arranged by a new cohort of medical students for their DPAS course.…”
Section: Abstract R é S U M émentioning
confidence: 99%
“…tions" [8]. In 2012, a group of UBC medical students participated in prison health care through DPAS and worked in direct contact with this marginalized population.…”
Section: Abstract R é S U M émentioning
confidence: 99%
“…This population health course addresses topics such as the social determinants of health, the patient-doctor relationship, ethics, community and public health, culture, addiction medicine, and health disparities [1]. The aim of the course is to cultivate social accountability and develop intrinsic CanMEDS roles (Scholar, Communicator, Collaborator, Manager, Health Advocate, and Professional) in medical students through core readings, lectures, online modules, seminars, and three different activity options [2,3].…”
Section: Introductionmentioning
confidence: 99%